2018
DOI: 10.1609/aaai.v32i1.12008
|View full text |Cite
|
Sign up to set email alerts
|

DeepType: Multilingual Entity Linking by Neural Type System Evolution

Abstract: The wealth of structured (e.g. Wikidata) and unstructured data about the world available today presents an incredible opportunity for tomorrow's Artificial Intelligence. So far, integration of these two different modalities is a difficult process, involving many decisions concerning how best to represent the information so that it will be captured or useful, and hand-labeling large amounts of data.DeepType overcomes this challenge by explicitly integrating symbolic information into the reasoning process of a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(23 citation statements)
references
References 11 publications
0
23
0
Order By: Relevance
“…Due to the significant growth in the size of KGs in recent years, there is an active line of research on designing systems that can handle large-scale training of KG embeddings, such as Marius [16,19], Pytorch Biggraph [15], and DGL-KE [24]. Various semantic annotation tasks, including entity linking and disambiguation, have received renewed interest from the research community, especially for deep learning based approaches [8,13,14,17]. Prior works have also discussed the applications of semantic annotations to enrich webpages for improved question answering and web search [1].…”
Section: Related Workmentioning
confidence: 99%
“…Due to the significant growth in the size of KGs in recent years, there is an active line of research on designing systems that can handle large-scale training of KG embeddings, such as Marius [16,19], Pytorch Biggraph [15], and DGL-KE [24]. Various semantic annotation tasks, including entity linking and disambiguation, have received renewed interest from the research community, especially for deep learning based approaches [8,13,14,17]. Prior works have also discussed the applications of semantic annotations to enrich webpages for improved question answering and web search [1].…”
Section: Related Workmentioning
confidence: 99%
“…However, the proposed frameworks did not deal with entity linking to existing domain standards for semantic interoperability. Other methods focusing on entity linking considered the existence of a knowledge graph without dealing with the cold start problem by constructing a knowledge graph from the beginning, where there is no available information on an instance level (Ganea & Hofmann, 2017;Raiman & Raiman, 2018). Towards this regard, Rossanez et al (2020) proposed an approach for knowledge graph construction from biomedical scientific articles.…”
Section: Related Workmentioning
confidence: 99%
“…Knowledge bases often group entities into semantic types, which inform several downstream NLP tasks such as coreference resolution [29], relation extraction [30], question answering [31], and language modeling [32]. Recent studies have shown that finegrained entity type prediction improves entity linking in Wikipedia text [33,22], indicating a clear potential for type prediction as a standard component of entity linking pipelines.…”
Section: Related Workmentioning
confidence: 99%
“…AttentionNER [77] utilizes attention mechanism for extracting relevant information from the context of a mention for type prediction. DeepType-FC and DeepType-RNN are two neural network based models proposed by [22] for entity typing. Type-CNN [78] is another neural approach which utilizes CNNs for modeling the global context of a mention for type prediction.…”
Section: Type Prediction Baselinesmentioning
confidence: 99%
See 1 more Smart Citation